Governance Transformation in Indonesian Islamic Higher Education: Autonomy, Institutional Reform and Global Competitiveness - Budi Waluyo (UIII Press, 2026)
This article examines how autonomy and institutional reform shape global competitiveness in Indonesian Islamic higher education. It asks how Islamic higher education institutions understand global competitiveness, how governance arrangements shape institutional reform, and what challenges emerge when autonomy, religious identity and international academic expectations intersect. Drawing on a qualitative comparative case study of three Islamic higher education institutions, this article examines how different governance arrangements, i.e. semi-autonomous public university (BLU), legal-entity public university (PTN-BH), and Muhammadiyah-affiliated private university, shape institutional strategies and responses to global competitiveness. The findings show that global competitiveness is not understood through a single model. In the semi-autonomous public university, competitiveness is framed as gradual institutional upgrading; in the legal-entity public university, it is framed as international positioning from inception; and in the Muhammadiyah-affiliated private university, it is framed as substantive international engagement rooted in social and religious mission. The article further shows that autonomy creates organizational space for reform, but does not automatically produce research capacity, international visibility, or academic excellence. Semi-autonomous governance provides limited flexibility under strong state supervision; legal-entity governance expands discretion while shifting sustainability risks to the university; and Muhammadiyah-affiliated private governance enables agility while intensifying dependence on tuition, foundation authority and market positioning. The article argues that governance transformation in Islamic higher education involves negotiated adaptation rather than convergence toward a single global model.